**Solution:**

[3*x*^{2}−*a*(2*x*−3*a*)]^{3}=(3*x*^{2})^{3}−3*C*1(3*x*^{2})^{2}.*a*(2*x*−3*a*)+3*C*2(3*x*^{2})*a*^{2}(2*x*−3*a*)^{2}−*a*^{3}(2*x*−3*a*)^{3}

⇒27*x*^{6}−27*x*^{4}*a*(2*x*−3*a*)+9*x*^{2}*a*^{2}(4*x*^{2}−12*a**x*+9*a*^{2})−*a*^{3}(8*x*^{3}−3×4×*x*^{2}×3*a*+3×2*x*×9*a*^{2}−27*a*^{3})

⇒27*x*^{6}−54*x*^{5}*a*+81*a*^{2}*x*^{4}−108*a*^{3}*x*^{3}+81*a*^{4}*x*^{2}−8*a*^{3}*x*^{3}+36*a*^{4}*x*^{2}−54*a*^{5}*x*+27*a*^{6}

⇒27*x*^{6}−54*x*^{5}*a*+117*a*^{2}*x*^{4}−116*a*^{3}*x*^{3}+117*a*^{4}*x*^{2}−54*a*^{5}*x*+27*a*^{6}